Analisis Kontrastif Dialek Gayo Uken dan Toa - Rifa Sabila Utami; Charles Butar-Butar (Medan Resource Center, 2023)
The differences between the Uken and Toa dialects are easily identified in the speakers' daily conversations. Speakers of these two dialects are still easy to understand each other. The difference occurs in some vowel sounds, intonation, some vocabulary, and some greetings in everyday dialogue. The objectives to be achieved in this study are to determine the differences between the Gayo Uken and Toa dialects. The research method used is a qualitative research method, this research was conducted using a descriptive analysis method. The difference in conversation between Uken and Toa people can be seen in terms of their pronunciation in interacting. The difference between the two Gayo dialects is in the form of words that are similar between the gayo uken and toa dialects but have the same meaning and what distinguishes these two dialects is the way they are pronounced. And based on the pronunciation of the Uken and Toa dialects spoken by the community, there are many phoneme variations, each word conveyed produces differences in vowel phonemes and consonant phonemes.